Report of the 17th Annual International Scientific Conference of the Montenegrin Sports Academy "Sport, Physical Activity and Health: Contemporary Perspectives" - Fatim Arifi (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The article is providing highlights of the Report of the 17th Annual International Scientific Conference of the Montenegrin Sports Academy "Sport, Physical Activity and Health: Contemporary Perspectives", hosted by the Montenegrin Sports Academy. The event was held on April 2-5, 2019 in Montenegro. The conference was held online, as a Video Conference, from the Montenegro, organized by the Montenegrin Sports Academy, and with the technical support of the Center of Information System (CIS). The participants of the conference were welcomed by Associate Professor Stevo Popovic, dean of the Faculty for Sport and Physical Education, University of Montenegro via Zoom application. This prestigious event gathered about 200 scientists from 46 countries.